2001
DOI: 10.1046/j.1365-2893.2001.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting response to initial therapy with interferon plus ribavirin in chronic hepatitis C using serum HCV RNA results during therapy

Abstract: In patients with chronic hepatitis C, 48 weeks of therapy with interferon (IFN) plus ribavirin results in a sustained virologic response of 40%. Preliminary analysis suggests that measuring HCV RNA at week 24, rather than week 12, might provide the best prediction of treatment response. To assess the clinical utility of serum HCV RNA determinations at different times during therapy as a predictor of a sustained virologic response we evaluated 912 treatment-naïve patients. Patients were randomized to receive IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…SVR is defined as undetectable HCV RNA 24 weeks after the cessation of treatment (12). Treatment for chronic HCV infection has evolved from interferon monotherapy, which results in a disappointing SVR rate of 10 to 20% (29), to combination therapy with interferon plus ribavirin, which is associated with a higher SVR rate of nearly 40% (27,36). Optimal therapy is now considered to be weekly pegylated interferon plus daily ribavirin, with SVRs reported in more than half of the patients treated (SVR rate, 54%) (26).…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…SVR is defined as undetectable HCV RNA 24 weeks after the cessation of treatment (12). Treatment for chronic HCV infection has evolved from interferon monotherapy, which results in a disappointing SVR rate of 10 to 20% (29), to combination therapy with interferon plus ribavirin, which is associated with a higher SVR rate of nearly 40% (27,36). Optimal therapy is now considered to be weekly pegylated interferon plus daily ribavirin, with SVRs reported in more than half of the patients treated (SVR rate, 54%) (26).…”
Section: Therapymentioning
confidence: 99%
“…For patients receiving interferon monotherapy, American and European consensus conferences recommended the cessation of treatment for patients with detectable HCV RNA after 12 weeks of therapy (12,29). For patients receiving interferon plus ribavirin, week 24 is considered the most accurate time to assess the response and consider the cessation of therapy, since 10% of patients with detectable HCV RNA at 12 weeks will attain an SVR (27). A recent analysis of patients participating in three trials of pegylated alfa-2a interferon suggested that a decision to stop treatment could be made as early as week 12 if there is detectable HCV RNA or a Ͻ2-log 10 drop in RNA levels (24).…”
Section: Therapymentioning
confidence: 99%
“…2,5 Several pre-treatment and on-treatment predictors of response to PR therapy including demography, disease status, viral load and genotype, have been used to individualize treatment and duration of therapy. [9][10][11][12][13] Recently, however, there has been a paradigm shift in pretherapy predictors of response to therapy in chronic HCV infections. Single nucleotide polymorphisms of the IL28B gene on chromosome 19 encoding interferon lambda have emerged as an important determinant of treatment response and spontaneous clearance of HCV.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to HCV genotype several clinical factors correlate with failure of interferon therapy including high viral load, obesity, and increased age (McHutchison and Hoofnagle, 2000). The magnitude of decrease in viral load initially after beginning interferon therapy correlates well with successful therapy (Davis et al, 2003;McHutchison et al, 2001;Terrault et al, 2005) yet little is known about the specific molecular factors that affect the alternate magnitudes of viral load decrease following induction of interferon/ribavirin therapy.…”
Section: Introductionmentioning
confidence: 99%